Bifurcation/chaos and their practical relevance to chemical and biological systems - Elnashaie, Said Salah Eldin Hamed (Universiti Putra Malaysia Press, 2014)
Bifurcation and chaos are important phenomena affecting many physical and chemical systems. They are also related to the stability/instability and multiplicity phenomena associated with these systems. The phenomena are not only of theoretical/mathematical interest but are also important for laboratory, pilot plant and commercial units. This paper concentrates on 3 systems: 1. The novel auto-thermic Circulating Fluidized Membrane Steam Reformer (CFBMSR) for the efficient production of the clean fuel hydrogen and which shows multiplicity of the steady state (static bifurcation). 2. A novel fermentor for the efficient production of bio-ethanol that shows static/dynamic bifurcation as well as chaotic behaviour. 3. The neurocycle of the acetylcholine transmitter in the brain using diffusion-reaction models in order to gain insight into their possible connection to Alzheimer and Parkinson Diseases (AD/PD); these are preliminary efforts to investigate the bifurcation and chaotic behaviour of this neurocycle.